Fish Cake Odeng Formulation from Catfish (Clarias batrachus) Surimi with Addition of Rice Anchovy (Stolephorus commersonnii) Flour as a Snack for Adolescents - Nursalastrie Nursalastrie; Nur Afrinis; Widawati Widawati (Journal of Nutrition Science, 2025)
Adolescents are vulnerable to nutritional problems such as calcium deficiency, which may impair bone growth and height. This study aimed to evaluate the characteristics of fish cake odeng made from catfish (Clarias batrachus) surimi with the addition of rice anchovy (Stolephorus commersonnii) flour in terms of nutritional content and organoleptic properties. A Completely Randomized Design (CRD) with one control (F0: 0%) and two treatments (F1: 9% and F2: 18%) was applied. Analyses included organoleptic tests, proximate composition, and calcium content. The results showed that F1 was the most preferred formulation according to panelists. The best formulation (F1) contained 20.2% moisture, 1.2% ash, 12.2 g protein, 8.7 g fat, 20.4 g carbohydrates, and 23.4 mg/100 g calcium, equivalent to 1.9% of the Recommended Dietary Allowance (RDA) for adolescents. Although the calcium content was low, the protein level met the criteria as a protein source, and the product provided 10% of daily energy needs (215 kcal) in 3–4 pieces. In conclusion, the fish cake odeng developed in this study met the criteria for a protein-source snack and contributed to energy intake, but did not qualify as a calcium source. Further studies are recommended to improve processing methods and formulations to enhance its calcium content.